Artificial Affection? Investigating AI-Generated Messages in Human Connections – Sender and Receiver Perceptions - Arooba Arshad,; Iftikhar Alam Khan,; Usman Ahmad,; Arshiya Subhani,; Mary Gella, (Technium: Romanian Journal of Applied Sciences and Technology, 2025)
Purpose: The increasing use of AI-generated messages in personal communication raises questions about emotional authenticity, trust, and perceived sincerity. This study explores the perspectives of both senders and receivers of AI-generated messages, with an emphasis on their usage patterns, emotional impact, and ethical considerations. Methodology: A mixed-method approach was employed, integrating qualitative insights with quantitative survey data. By targeting both individuals - those who use AI for personal messages and those who receive them - two distinct survey questionnaires were distributed to assess how senders and receivers perceive things differently. Findings: This study shows that although AI offers convenience and improved writing quality, they lack emotional nuance and customization. A sizable percentage of receivers can identify AI-generated messages and believe that they undermine the sender’s credibility. Furthermore, most senders do not reveal the use of AI which indicates worries about dishonesty or perception of AI as merely a writing tool. Novelty: This study offers a distinctive comparative analysis of AI-generated messages from the perspectives of both the senders and receivers. Unlike prior studies that mostly focus on AI’s technical abilities, this study explores the social and emotional implications of AI-assisted communication. Implications: The results imply that although AI has a role in digital communication, its use in private correspondences should be limited to prevent interactions from becoming less genuine. Transparency regarding AI involvement in communication could help bridge the gap between convenience and authenticity in AI-assisted messaging.